Optical Pattern Recognition XXII 2011
DOI: 10.1117/12.883669
|View full text |Cite
|
Sign up to set email alerts
|

The concept models and implementations of multiport neural net associative memory for 2D patterns

Abstract: The paper considers neural net models and training and recognizing algorithms with base neurobiologic operations: p-step autoequivalence and non-equivalenc The Modified equivalently models (MEMs) of multiport neural net associative memory (MNNAM) are offered with double adaptive -equivalently weighing (DAEW) for recognition of 2D-patterns (images). It is shown, the computing process in MNNAM under using the proposed MEMs, is reduced to two-step and multi-step algorithms and step-by-step matrix-matrix (tensor-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…These signals are actually coefficients β in appropriate models described in Section 2.1. If the models use only weighing by this coefficient β of appropriate weighting matrix or tensor synapse connections, as it has been shown in papers 5,10,12,16 , increasing the k-order of nonlinear transformations are necessary for improving adaptation and increasing the quality of the similarity measure determination of images. If the models use the additional weighing of matrices or tensors connections array of coefficients α (vector for vector or matrix for 2D input data) according to formula (1), in architecture, as seen in Fig.…”
Section: Adapting Optical Multiport Architecture Of Associative Memormentioning
confidence: 97%
See 4 more Smart Citations
“…These signals are actually coefficients β in appropriate models described in Section 2.1. If the models use only weighing by this coefficient β of appropriate weighting matrix or tensor synapse connections, as it has been shown in papers 5,10,12,16 , increasing the k-order of nonlinear transformations are necessary for improving adaptation and increasing the quality of the similarity measure determination of images. If the models use the additional weighing of matrices or tensors connections array of coefficients α (vector for vector or matrix for 2D input data) according to formula (1), in architecture, as seen in Fig.…”
Section: Adapting Optical Multiport Architecture Of Associative Memormentioning
confidence: 97%
“…This can be achieved only with corresponding architectures based on optical and optoelectronic realization with spatial and time integration 10,12 . In paper 16 it was shown that the optoelectronic architecture with time integration can provide significant benefits and performance 10 9 -10 10 connections per second and they can be used to realize and multiport autoassociative and multiport heteroassociative memory (MNNAAM and MNNHAM).…”
Section: Adapting Optical Multiport Architecture Of Associative Memormentioning
confidence: 99%
See 3 more Smart Citations